Ceria-Based Materials for Thermocatalytic and Photocatalytic Organic Synthesis - Huang, Xiubing; Zhang, Kaiyue; Peng, Baoxiang; Wang, Ge; Muhler, Martin; Wang, Feng (ACS catalysis, 2021)
Value-added chemicals, fuels, and pharmaceuticals synthesized by organic transformation from raw materials via catalytic techniques have attracted enormous attention in the past few decades. Heterogeneous catalysts with high stability, long cycling life, good environmental-friendliness, and economic efficiency are greatly desired to accomplish the catalytic organic transformations. With the advantages of reversible Ce3+/Ce4+ redox pairs, tailorable oxygen vacancies, and surface acid–base properties, ceria-based catalysts have been actively investigated in the fields of catalytic organic synthesis. In this Review, we summarize the fundamentals and latest applications of ceria-based heterogeneous catalysts for organic transformations via thermocatalytic and photocatalytic routes. The fabricating approaches of various ceria and ceria-based catalysts and their structure/composition–activity relationship are discussed and prospected. The advanced characterization techniques and theoretical methods for reaction mechanism studies over CeO2-based catalysts are summarized and discussed. This comprehensive Review provides a basic understanding of the structure–performance relationships of ceria-based catalysts for organic synthesis. In addition, it also provides some insights and outlooks in the design and research direction in the ceria-based catalysts with better performance.